Variasi Kejadian Stunting Usia 6 - 24 Bulan menurut Karakteristik Keluarga, Orang Tua, dan Anak - Demsa Simbolon; Ina Debora Ratu Ludji; Beatrix Soi (Jurnal Kesehatan Manarang, 2021)
Child stunting is a global problem, including in Indonesia. The variation of stunting prevalence in Indonesia is very wide between provinces, but the interventions carried out tend to be the same. Variations in stunting prevalence at the stunting locus according to family, mother and child characteristics need to be known as an evidence based in planning appropriate intervention efforts. The study used a cross sectional design which aims to determine the variation in the proportion of stunting according to the characteristics of parents, families and children aged 6 – 24 months in South Central Timor District (TTS) and North Bengkulu District (BU). The research was conducted in June-November 2019. The population is all stunting children aged 6 – 24 months. The sample was selected by purposive sampling with inclusion criteria, namely stunting children, children aged 6 – 24 months, biological children, single births, no defects, and no comorbidities. The total sample was 120 stunting children aged 6 – 24 months, consisting of 60 stunting children in BU District and 60 stunting children in TTS District. The research instrument used a structured questionnaire. Data analysis used homogeneity test with chi square test. The results showed a high proportion of stunting in small families, while based on socio-economic heterogeneous families in both districts. In BU District, 30% of stunting children came from pre-prosperous families and 56.7% occurred in small families, while in TTS District all (100%) stunting children came from poor families and 65% from small families. The proportion of stunting was higher in mothers with normal height, age at the time of marriage 20 – 35 years, education of fathers and mothers were middle to high, mothers did not work, and fathers worked, children were born with normal weight, normal birth length, received breastmilk initiation, and exclusively breastfed. Stunting can occur in all families, so efforts are needed to improve family characteristics, parents and birth history to prevent stunting in Indonesia.